![\frac{4x + 3}{4} - \frac{x - 2x - 1}{3} = \: x + \frac{1}{3} \frac{4x + 3}{4} - \frac{x - 2x - 1}{3} = \: x + \frac{1}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B4x+%2B+3%7D%7B4%7D++-+%5Cfrac%7Bx+-+2x+-+1%7D%7B3%7D++%3D++%5C%3A+x+%2B++%5Cfrac%7B1%7D%7B3%7D+)
what will be the answer?
Answers
Answered by
0
Answer:
f2f r cut c hi fruity h y I g if uhh g uhh f y f
Answered by
0
Answer:
x= -3/16
Step-by-step explanation:
In the pic above
Attachments:
![](https://hi-static.z-dn.net/files/dee/bc4eac9f09523eee223bd377ae796287.jpg)
Similar questions